Hollywood [compact disc, unabridged] : a third memoir - McMurtry, Larry (Recorded Books, 2011)
McMurtry presents the final installment in his memoir trilogy. Tinged with his wry humor and Texas swagger, Hollywood is McMurtry's anecdote-filled take on Tinseltown from the year his Horseman, Pass By was adapted into Hud (1963) to the year he wrote the screenplay for the Oscar-winning Brokeback Mountain (2005).